A organização retórica do pôster acadêmico sob a perspectiva da análise crítica de gênero - Mozzaquatro, Luziane Boemo (2014)
Successful participation in a discursive genre a recurrent human activity, culturally situated, mediated by semiotic resources and practiced for specific purposes demands an array of diverse knowledges, starting from the production, circulation and consumption conditions of the genre up to the elements that constitute its textual materiality (visual and verbal language). In the academic universe, different discursive genres demand this kind of knowledge from the participants. Among them, the academic poster, a genre that represents a visual and a very summarized version of an academic article (MACINTOSH-MURRAY, 2007). After these considerations, this research aims to investigate the academic poster as a multimodal discursive genre, analyzing the role of verbal and non verbal languages in the constitution of the rhetorical organization of the poster, in order to offer guidelines for the elaboration and the reading of this genre in the academic context. We start from the theoretical-methodological reference of Critical Genre Analysis (MOTTA-ROTH, 2008), according to which the study of discursive genres necessarily considers two research dimensions: text and context . Thus, the corpus includes as text , 8 academic posters of the Linguistic/Languages and Biological Science areas, presented in the 27th Integrated Academic Journey of the Federal University of Santa Maria/RS, in 2012; and, as context , 34 interviews conducted with academic posters authors context of production and with readers (evaluators) context of consumption of this genre, participants in the event. Contextual analysis indicated that academic poster is considered predominantly a genre whose textual organization approaches to the scholarly article, with more intense exploitation of image posters Biosciences than posters of Letters, as attractive and presentation of information resource. These contextual data, among others, helped in the reading and interpretation of functional textual elements (verbal and nonverbal) in the configuration of the rhetorical organization of the corpus posters. The analysis showed the functional organization of the academic poster genre in seven rhetorical movements: Movement 1 Identify the Research; Movement 2 Situate the Research; Movement 3 Present the Research; Movement 4 Describe the Methodology; Movement 5 Present the Result(s); Movement 6 Discuss the Research; Movement 7 Indicate Bibliographic References. Besides the verbal language, the non verbal language showed significance in the configuration of Movements 5 Present the Result(s) and 6 Discuss the Research, and, in the case of Biological Science, the non verbal language predominated in Movement 5 Present the Result(s). Thus, these movements, associated with the roles of verbal and non verbal languages, indicate how the academic posters realize their communicative purpose of presenting a research in a summarized form. The results point to the fact that the participation in the academic poster genre demands multiliteracies, at least in the context of the UFSM.